LAW ENFORCEMENT PROHIBITION OF COLLECTING DONATIONS IN SURABAYA CITY STREET - Trislia, Gandhini Eka (NOVUM : JURNAL HUKUM, 2019)
Article 34 Regional Regulation Surabaya No. 2 of 2014 on the Implementation of Public Order and Peace Society prohibits any individual or entity conducting the collection of donations on the street without permission. Following up on the mayor of Surabaya to coordinate with related agencies regarding the donation collection activity permit conditions on the road. Related assistance to social should not be done on the road, while in terms of aid for natural disasters can be done on the road - the road that are allowed for activities donation collection on the road, but based on the data collected by the news online in Surabaya still encountered the activities of collecting donations in road carried out on the road - the road that are not allowed. The purpose of this study was to determine the enforcement by the Department of Social Welfare and Disaster Management Agency and Public Protection together with the Civil Service Police Unit against the perpetrators of collecting donations in the city of Surabaya. As well as to determine the constraints experienced by the Social Service and Disaster Management Agency and Public Protection together with the Civil Service Police Unit in performing law enforcement against collecting donations in the city of Surabaya. This research uses socio-juridical research. Collecting data in this study was conducted with interviews and documentation related to license collecting donations on the street. Data will be analyzed by qualitative analysis by using step - step interactive analysis. The results showed that law enforcement against collecting donations in the city of Surabaya is not done well for law enforcement only provide sanctions against the perpetrators of disturbing public order reported by the community alone and do inaction when there are no reports from the public. The constraints in law enforcement efforts against the perpetrators of collecting donations in the city of Surabaya, among others, is the lack of coordination between the Department of Social Welfare, Disaster Management Agency and Public Protection and Civil Service Police Unit of Surabaya, Official Web Social Service inactive, as well as the Regional Regulation Surabaya city No. 2 of 2014 on the Implementation of Public Order and Peace Communities that do not clearly regulate the sanctions. Â  Â  Keywords: Law enforcement, Prohibition, Donation collection on the road